Analisis Fungsi Shuujoshi Dalam Anime Doraemon Stand By Me 1 - Winda Surya; Rita Arni (Universitas Negeri Padang, 2023)
Shuujoshi is a particle located at the end of a sentence that is used to show the speaker's feelings. The use of shuujoshi or sentence ending particles is very difficult to find in other languages in the world. Shuujoshi is often found in informal conversations, for example in anime. Shuujoshi have various functions and meanings. In one sentence shuujoshi there are several different functions. Researchers assess the importance of research that analyzes shuujoshi in anime, so that there is no misunderstanding of students. The purpose of this research is to find out what are the functions of shuujoshi in the anime Doraemon Stand By Me 1. The research design used is a qualitative research with descriptive method. The data in this study are sentences that use the shuujoshi function in the anime Doraemon Stand By Me 1 based on the theory of Chino (1991). The source of data in this study is the anime Doraemon Stand By Me 1. The instrument of this research is the researcher himself. Based on the results of the research conducted, the researchers found 4 functions of shuujoshi na and 6 functions of shuujoshi ne in the anime Doraemon Stand By Me 1 by Fujiko F. Fujio based on Chino's theory (1991). The shuujoshi na function that is not found in the anime Doraemon Stand By Me 1 is the function of asking other people for approval.